Qualitative synthesis of young people's views of sex and relationship education. (13th November 2015) - Pound, Pandora; Langford, Rebecca; Campbell, Rona
Abstract: Background: Sex and relationship education (SRE) is a contested issue but debate is dominated by professionals, parents, and the media. We aimed to investigate young people's experiences of SRE. Methods: We searched for qualitative studies published between Jan 1, 1990, and Feb 17, 2015, of young people's views of SRE using the terms "adolescent", "young people", "sex and relationships", education", "sex education", "sexual health education", "qualitative research", "qualitative" (Medline, Embase, PsychINFO); and "adolescent", "child", "view", "perception", "experience", "sex education", "SRE", "sexual health education", "school", "qualitative" (Sociological Abstracts, IBSS, ERIC, Web of Science, CINAHL). Hand searches were also conducted. No language restrictions were imposed. We included studies with students aged 4–19 years in full-time education, young adults aged 19 or younger, or adults 25 years old or younger if recalling SRE; qualitative methods of data collection and analysis; and school-based or linked SRE. We excluded studies focusing solely on HIV/AIDS and studies of students with special needs. References found electronically were double screened and eligible papers appraised by two independent reviewers using criteria derived from reviewing qualitative research appraisal checklists. Data were extracted from included papers by the same two independent reviewers and synthesised using a meta-ethnographic approach. Findings: 31 relevant publications were identified electronically (from a total of 539), and 37 by hand-searching. Of these 68 publications, 54 remained after quality appraisal (47 studies). Young people reported receiving negative, gendered, and heterosexist content that ignored the fact and diversity of their sexual activity and failed to provide information they wanted. Students were vulnerable during SRE, with young men anxious to conceal sexual ignorance and young women risking sexual harassment if they participated. Both wanted a safer environment in SRE and some young women expressed a preference for single sex classes. Students were positive about sexual health experts and peer educators but disliked having their own teachers deliver SRE because of blurred boundaries, lack of anonymity, teachers' embarrassment, and poor training. The appendix gives examples of young people's quotes. Interpretation: Young people should be involved in developing SRE programmes. SRE content should be unbiased, positive, and reflect sexual diversity and the fact of many young people's sexual activity. SRE should take place in a safe environment and be delivered by experts, probably from outside school. Funding: National Institute for Health Research School for Public Health Research.